Removal of Ranitidine Using Chlorella Sorokiniana MH923013 - Makki, Maha Jawdat; Al-Mashhadani, Mahmood K. H.; Al-Dawery, Salam K. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The frequent and widespread use of medicines and personal care products, particularly in the residential environment, tends to raise concerns about environmental and human health impacts. On the other hand, carbon dioxide accumulation in the atmosphere is a problem with numerous environmental consequences. Microalgae are being used to bioremediate toxins and capture CO2. The current study aimed to confirm the possibility of removing pharmaceutical contaminant (Ranitidine) at different concentrations by using the Chlorella Sorokiniana MH923013 microalgae strain during the growth time. As part of the experiment, carbon dioxide was added to the culture medium three times per week. Explanatory results revealed that gas doses directly affect microalgae growth and removal efficiency, as evidenced by faster and more productive cell adaptation compared to control cultures. The development profile of microalgae is significantly influenced by pure carbon dioxide bubbles. When compared to control flasks, carbon dioxide increased the specific growth rate and doubling time. During the 312 hours microalgae cultivation period, the Chlorella strain recorded the highest pollutant removal efficiency (58%), particularly at the pollutant concentration of 5 mg/l CO2.